2019
DOI: 10.3390/en12214190
|View full text |Cite
|
Sign up to set email alerts
|

Levitation Methods for Use in the Hyperloop High-Speed Transportation System

Abstract: The Hyperloop system offers the promise of transportation over distances of 1000 km or more, at speeds approaching the speed of sound, without the complexity and cost of high-speed trains or commercial aviation. Two crucial technological issues must be addressed before a practical system can become operational: air resistance, and contact/levitation friction must both be minimized in order to minimize power requirements and system size. The present work addresses the second issue by estimating the power requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…It depends on the vertical and horizontal position and forwarding velocity of the bogie. So that the capsule's nonlinear dynamics of a quarter-car model is defined as a combination of linear and nonlinear parts, as shown in equation (5).…”
Section: Quarter-capsule Vehicle Semi-active Suspension System Nonlinear Dynamic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It depends on the vertical and horizontal position and forwarding velocity of the bogie. So that the capsule's nonlinear dynamics of a quarter-car model is defined as a combination of linear and nonlinear parts, as shown in equation (5).…”
Section: Quarter-capsule Vehicle Semi-active Suspension System Nonlinear Dynamic Modelmentioning
confidence: 99%
“…1 To eliminate this problem many researchers have been doing research to invent a new suspension system. One of the potential options, air bearing suspension, 5 was tested but it is found to be not good for onboard passengers' comfort. 1 Enormous researchers have proposed magnetic levitation and concluded that the system is most appropriate for levitation and propulsion of advanced ground transportation systems such as high-speed train and hyperloop capsule, though the cost of construction is prohibitive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system consists of a low-pressure tube with capsules traveling at both low and high speeds throughout the length of the tube using levitation [8]. The time spent traveling during short journeys at cruise speed is much lower compared to the overall end-to-end travel time in air transportation due to the inefficiencies in air travel (runway taxiing, climb, descent, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also an electrodynamic type of levitation, where a vehicle equipped with a magnetic field source repels from the electrically conductive track [1,4,5]. Electrodynamic suspension (EDS) systems may be based on permanent magnets arranged in a Halbach array and are perfect for application in high-speed magnetically levitating trains (maglevs [6,7] and hyperloops [8,9]) because of their construction simplicity and linearly increasing lift-to-drag ratio with velocity. However, at relatively low speeds (below 300 km/h) electrodynamic systems such as Inductrack generate high drag forces when compared with a classic nonmagnetic high-speed railway [10][11][12].…”
Section: Introductionmentioning
confidence: 99%